Drug Interactions For Pulmonary Tuberculosis Patients In Dr. Wahidin Sudirohusodo Makassar Hospital - Andi Ulfah Magefirah Rasyid , Zulham, Herlina Rante, Irawaty Djaharuddin (STIFA Makassar, 2016)
Tuberculosis (TB) is a chronic disease that poses a health problem in the world, including Indonesia. The aim the research is to identify the interaction of anti-tuberculosis drug (OAT) with nonOAT and other medications in addition to OAT given to patients of pulmonary tuberculosis at Dr. Wahidin Sudirohusodo Makasar hospital. This research used descriptive study design with a retrospective data carried out at Dr. Wahidin Sudirohusodo Makasar hospital. The research design was descriptive study with a retrospective data. Data were collected from medical records of patients with pulmonary tuberculosis in inpatients who were given treatment from January to September 2015. The result shows that among the positive pulmonary tuberculosis patients there were 24 males (61.5%) and 15 females (38.5%). The most prevalent drug interaction was significance level 4 with 36 cases (42.35%), there were 67 cases (78.82%) of delayed onset, and 54 cases (63.53%) of moderate severity interaction. The most interaction mechanism was pharmacokinetic interaction with 74 cases (87.1%) out of 85 total number of cases who experienced drug interactions.